Pelaksanaan Penyidikan dan Perlindungan Hukum dalam Tindak Pidana Perdagangan Orang yang Dilakukan oleh Anak di bawah Umur : Studi Kasus Unit PPA Polresta Bukittinggi - Kuky Andean Shintong Siagian (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the investigation process involving children as perpetrators of trafficking in persons at the Women and Children Protection Unit (PPA) of Bukittinggi Police Resort and to assess the forms of legal protection provided at each stage of the examination. This research applies an empirical juridical approach by combining literature review and field research through interviews with investigators and related parties. The findings indicate that the investigation process has been conducted in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, while upholding the principle of the best interests of the child. Legal protection is implemented through legal assistance, closed hearings, limited detention periods, and coordination with relevant institutions to support the child’s recovery and rehabilitation. However, several obstacles remain, including the limited number of investigators, restricted investigation timeframes, and difficulties in presenting witnesses. This study concludes that legal protection for children involved as perpetrators of trafficking in persons has been carried out in line with normative regulations, yet it requires strengthened institutional capacity and inter-agency coordination to ensure more effective implementation.